Effect of digital transformation on innovation performance in China: corporate social responsibility as a moderator - Wang, Lei; Yan, Jinzhe (Frontiers in Environmental Science, 2023)
Introduction: In the digital economy, digital transformation (DT) is a deliberate decision to improve organizational procedures, alter production processes, introduce precision marketing, and more, ultimately impacting how well businesses innovate. This is why the current article investigates the effect of DT and the firm's innovation performance and the boundary condition of corporate social responsibility (CRS). Method: This study proposed a conceptual research model for the effect of DT on innovation performance and discussed the boundary condition of CRS. We collected China’s listed A-share firms’ data to examine the proposed hypotheses statistically. After Hausman test, the current study adopted fixed-effect regression, examined the heterogeneity issues resulting from different industry classifications, and robustness test for the correctness of the results. Results and Implications: The following main conclusions are drawn: (1) DT can significantly enhance product innovation performance; (2) DT can significantly improve process innovation performance; (3) There is a time lag effect on the innovation performance(both product and process innovation performance) of the previous period on the innovation performance of the current period; (4) CSR positively moderates the role of DT on innovation performance; and (5) The impact of DT is heterogeneous across industries and patent. This study not only enriched the literature on DT and innovation performance but also provided the guidelines to promote digital transformation at the firm level.